2015
DOI: 10.5194/acp-15-7819-2015
|View full text |Cite
|
Sign up to set email alerts
|

Changing shapes and implied viscosities of suspended submicron particles

Abstract: The change in shape of atmospherically relevant organic particles is used to estimate the viscosity of the particle material without the need for removal from aerosol suspension. The dynamic shape factors χ of particles produced by α-pinene ozonolysis in a flow tube reactor, under conditions of particle coagulation, were measured while altering the relative humidity (RH) downstream of the flow tube. As relative humidity was increased, the results showed that χ could change from 1.27 to 1.02, corresponding to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
162
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(178 citation statements)
references
References 51 publications
11
162
2
Order By: Relevance
“…COMSOL uses a finite element method and has a number of built-in modules that can be utilized to simulate a specific experimental condition. Recently, several research groups have employed COMSOL in atmospheric and aerosol chemistry studies Sellier et al, 2015;Y. Zhang et al, 2015).…”
Section: Cfd Simulationsmentioning
confidence: 99%
“…COMSOL uses a finite element method and has a number of built-in modules that can be utilized to simulate a specific experimental condition. Recently, several research groups have employed COMSOL in atmospheric and aerosol chemistry studies Sellier et al, 2015;Y. Zhang et al, 2015).…”
Section: Cfd Simulationsmentioning
confidence: 99%
“…In addition, mass concentrations of biogenic SOA are typically ≤ 10 µg m −3 in the atmosphere (Spracklen et al, 2011). As a starting point to quantify how often mixing times of organic molecules are < 1 h within α-pinene SOA generated using low, atmospherically relevant mass concentrations, we developed a temperature-independent parameterization using the room-temperature viscosity data for α-pinene SOA from Zhang et al (2015) (Table S5) and roomtemperature viscosity data for water from (Crittenden et al, 2012) (Table S3). Zhang et al (2015) measured the viscosity of α-pinene SOA over a range of relative humidities (0-60 %), and the SOA used in these experiments was generated in the laboratory using a mass concentration of ∼ 70 µg m −3 .…”
Section: Effect Of Mass Concentration Used To Generate the Soamentioning
confidence: 99%
“…As a starting point to quantify how often mixing times of organic molecules are < 1 h within α-pinene SOA generated using low, atmospherically relevant mass concentrations, we developed a temperature-independent parameterization using the room-temperature viscosity data for α-pinene SOA from Zhang et al (2015) (Table S5) and roomtemperature viscosity data for water from (Crittenden et al, 2012) (Table S3). Zhang et al (2015) measured the viscosity of α-pinene SOA over a range of relative humidities (0-60 %), and the SOA used in these experiments was generated in the laboratory using a mass concentration of ∼ 70 µg m −3 . The median room-temperature viscosities reported by Zhang et al are higher than the median room-temperature viscosities reported by Grayson et al (2016) using a mass concentration of 520 µg m −3 (Fig.…”
Section: Effect Of Mass Concentration Used To Generate the Soamentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly because viscosity, bounce factors and glass transition temperatures only provide indirect evidence for kinetic limitations of water diffusivity, whereas diffusion coefficients in the amorphous state span many orders of magnitude. Previous studies investigated the viscosity of atmospherically relevant model systems at around room temperature and used the StokesEinstein relation to derive diffusion coefficients (RenbaumWolff et al, 2013;Hosny et al, 2013;Power et al, 2013;Abramson et al, 2013;Booth et al, 2014;Zhang et al, 2015). However, diffusivity and viscosity decouple below approximately 1.2 T g or higher, where T g refers to the thermal glass transition temperature as measured by differential scanning calorimetry (Mapes et al, 2006;Corti et al, 2008).…”
mentioning
confidence: 99%